Commentary: Reflections on the Modern Chinese Legal System - William C. Jones (Washington University Law Quarterly, 1982)
This Article posits that one can usefully approach law in China, including labor law, from three points of view: those of Communism, the West, and Japan.
Keywords: Cultural norms; Labor law; China